El sistema de personajes de la novela “El árbol de la ciencia” de Pío Baroja - Santillán Guapulema, Victor Alexander (2025)
The research work was proposed with the general objective of characterizing the system of characters of the novel The Tree of Science by Pío Baroja from the philosophical postulates of rationalism and vitalism proposed by José Ortega y Gasset, one of the fundamental works for its innovation and strong criticism of a Spain in crisis at the beginning of the twentieth century. The methodology adopted responded to a qualitative approach, configuring it in a descriptive and bibliographic study, whose corpus of analysis was constituted by the literary work in question. For the analysis and interpretation of the information, analytical-synthetic, historical-logical and hermeneutical methods and content analysis techniques were used. The results of the research reflected the significant changes in people's philosophical thinking with rationalism and vitalism for a better understanding of the world around them. In addition, how the Generation of '98 offered brutal criticisms of Spain's political system through pessimism and national disenchantment, to generate changes in people and begin to look for solutions to rehabilitate the country; finally, the relationship of the character system embodied the challenges of Andrés Hurtado in facing an existential humanist crisis where the rationalism of Ortega y Gasset sought to create a balance so that life is lived and understood intuitively and logically.